Functional Impacts of Epitranscriptomic m6A Modification on HIV-1 Infection - Stacia Phillips; Tarun Mishra; Siyu Huang; Li Wu (Viruses, 2024)
Epitranscriptomic RNA modifications play a crucial role in the posttranscriptional regulation of gene expression. N6-methyladenosine (m6A) is the most prevalent internal modification of eukaryotic RNA and plays a pivotal role in RNA fate. RNA m6A modification is regulated by a group of cellular proteins, methyltransferases (writers) and demethylases (erasers), which add and remove the methyl group from adenosine, respectively. m6A modification is recognized by a group of cellular RNA-binding proteins (readers) that specifically bind to m6A-modified RNA, mediating effects on RNA stability, splicing, transport, and translation. The functional significance of m6A modification of viral and cellular RNA is an active area of virology research. In this review, we summarize and analyze the current literature on m6A modification of HIV-1 RNA, the multifaceted functions of m6A in regulating HIV-1 replication, and the role of viral RNA m6A modification in evading innate immune responses to infection. Furthermore, we briefly discuss the future directions and therapeutic implications of mechanistic studies of HIV-1 epitranscriptomic modifications.